A survey of woodward's counterfactual theory of causation (2011)
In his book Making Things Happen (2003), James Woodward proposes aninterventionist account of causation. Such account requires the adoption of a counterfactual analysis of causal claims. However, how should counterfactual claims be understood and interpreted from an interventionist standpoint? I will try to answer this question taking as a guide the influent ial account of counterfactuals presented by David Lewis in his famous paper "Causation" (1979). The aim of this paper is to outline some general considerations that show how Woodward's counterfactual analys is differs from Lewis's, thus gaining immunity against classical objections to Lewis's analysis, and to present some difficulties of Woodward's own approach. The paper is divided in three parts. First, I will present briefly the main ideas of the manipulability theory of causation; in the second part, I will introduce the necessity of adopting a counterfactual analysis in such an account, followed by a brief presentation of Lewis's theory as well as the differences and similarities with Woodward's approach. Finally, in the third part I will examine the notion of intervention, a key concept in the manipulability account, from the standpoint of counterfactual analysis, and present a problem with Woodward's overall account.